Unity in diversity : mysticism, messianism and the construction of religious authority in Islam - Mir-Kasimov, Orkhan. (Islamic History and Civilization, 2014)
What are the mechanisms of change and adaptation in Islam, regarded as a living organism, and how do they work? How did these mechanisms preserve the integrity of Muslim civilization through the innumerable hazards, divisions and devastations of time? From the perspective of history and intellectual history, this book focuses on a significant, though still largely under studied, aspect of this immense issue, namely, the role of mystical and messianic ferment in the construction and re-construction of religious authority in Islam. Sixteen scholars address this topic with a variety of approaches, providing a fresh outlook on the trends underlying the evolution of Muslim societies and, in particular, the emergence and consolidation of the Ottoman, Safavid and Mughal Empires. Contributors include: Abbas Amanat, Mohammad Ali Amir-Moezzi, Paul Ballanfat, Shahzad Bashir, Ilker Evrim Binbaş, Daniel De Smet, Devin DeWeese, Armin Eschraghi, Omid Ghaemmaghami, Ahmet T. Karamustafa, Todd Lawson, Pierre Lory, Matthew Melvin-Koushki, Orkhan Mir-Kasimov, A. Azfar Moin, William F. Tucker.